A study of factors and their influence on mathematics-related beliefs and performance in Turkey - Kandemir, Mehmet Ali; Eryilmaz, Nurullah; Shelley, Mack (Frontiers in Education, 2024)
The present study endeavors to uncover the intricate nexus among pertinent variables, including self-efficacy, perceived usefulness, parental education levels, and gender, and their relationship with mathematics performance. To achieve this objective, several hypotheses were tested, and a path model was estimated. The study cohort comprised 117 8th-grade students (64 females, 53 males) enrolled in a secondary school in Turkey. Results, in general, supported research hypotheses and the path model. Males' mathematics self-efficacy was found to be higher than females. No significant gender difference was found in the mathematics performance score in the initial analysis. Nevertheless, gender made a significant contribution to the prediction of mathematics performance beyond the effects of other variables in the hierarchical regression analysis. Consistent with theoretical predictions, females' mathematics self-efficacy expectations were unrealistically low compared to males. However, the effect of self-efficacy on performance was found to be invariant across gender. Perceived usefulness was found to be moderately correlated with performance but made little contribution to the prediction of performance above and beyond the effects of other variables.